Investment Feasibility Study for Iron Ore Mining Project (Case Study : PT Ina Touna Mining) - Adisaputra, Muhammad Rizky; Sukarno, Subiakto (The Indonesian Journal of Business Administration, 2013)
With increasing industry sector in Indonesia, lead to higher demand for industry raw materials especially in natural resources industry. PT. Ina Touna Mining, a national private company in Indonesia is conducting mineral exploration of iron ore in Tojo, Tojo Una Una regency, Central Sulawesi province for 8 years concession period. In its efforts to get the licence in conducting its business, author create the investment feasibility study which will calculate the cash flow in the 8 years concession period. To calculate the investment feasibility study, author uses capital budgeting approach, sensitivity analysis and risk handling management strategy.Â Keywords: iron ore, feasibility study, capital budgeting, sensitivity analysis, risk management